The treatment of Slaughterhouses wastewater by An Up Flow - Anaerobic Sludge Blanket (UASB) reactor. - Abdullah Saghir; Salwa Hajjar (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Slaughterhouse wastewater is heavily polluted. Itcontains a high concentration of oil and grease, phosphorus, nitrogen, organicmatter and suspended solids.Theobjective of the research is study the ability of slaughterhouses wastewatertreatment by a UASB reactor and define the best hydraulic retention time (HRT).This research focuses on the treatment of slaughterhousewastewater in Up Flow Anaerobic Sludge Blanket (UASB) reactor In thesereactors, the polluted wastewater rises slowly which allows it to form a suspendedsludge blanket. Granules of sludge gather on the surface and anaerobic bacteriais activated which feeds on the organic matter which exists in the liquid. The research includes a study of the effect of hydraulicretention time (HRT) on the efficiency of treatment in UASB reactors at a constanttemperature of about 30±1°C.The experiments have illustrated that it is possible to achieve excellentremoval efficiency for high concentrations of COD when the temperature of the wastewateris fixed at 30±1 °C. Theremoval efficiency fit with hydraulic retention times (HRTs) in UASB reactor, forthe following values of HRTs:(6,12,18,24,30,36) hours, the removal efficiencies of COD were:(35.78%,48.93%,56.15%,71.3% ,76.33%,83.37%) respectively.